Code-Switching in the Puella ID YouTube Channel by Cinta Laura - Oktaviani Grafika Sunarti; I Putu Andri Permana (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The phenomenon of code-switching is increasingly widespread due to the impact of social media such as YouTube, whose creators are bilingual. This study aims to identify the types of code-switching on Puella ID Youtube Channel by Cinta Laura and analyze the reason why the host and the speaker use code-switching in their conversation. In order to identify codeswitching, this research applied the theories proposed by Poplack (1980) as cited in Romaine (1989) to classify the types of Code-Switching and the second theory analysis of the reason for code-switching proposed by Hoffmann (1991). This study used the descriptive qualitative method. The end result of this research represented three types of code-switching and six out of seven reasons for code-switching were found. The dominant type that heaves in sight in this research is intra-sentential switching. Six reasons for codeswitching were found. The very dominant reason is the intention of clarifying the speech content for the interlocutor. The expression of the utterance is something used to point out something or also to lead up to connect between sentences or words so that it can easily be realized by the other person.